2014
DOI: 10.1155/2014/173084
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab Alone or Combined with Macular Laser Photocoagulation for Recurrent or Persistent Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: Background. To evaluate the efficacy of intravitreal bevacizumab (IVB) injection with or without macular laser photocoagulation (MLP) for recurrent or persistent macular edema (ME) secondary to branch retinal vein occlusion (BRVO). Methods. Thirty-four eyes underwent IVB injection for ME secondary to BRVO as a primary treatment. Twenty of the 34 eyes experienced recurrent or persistent ME after the first IVB. Nine of the 20 eyes (Group 1) were retreated with IVB combined with MLP. The remaining 11 eyes (Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Branch retinal vein occlusion (BRVO) is one of the major retinal vascular disorders causing vision loss [1,2], wherein macular edema (ME) is the main culprit for vision impairment. Until recently, the standard of care for ME was grid laser photocoagulation based on the branch vein occlusion (BVO) study [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branch retinal vein occlusion (BRVO) is one of the major retinal vascular disorders causing vision loss [1,2], wherein macular edema (ME) is the main culprit for vision impairment. Until recently, the standard of care for ME was grid laser photocoagulation based on the branch vein occlusion (BVO) study [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several small clinical trials reported that a combined intravitreal anti-VEGF injection and subsequent macular grid laser photocoagulation could reduce the required number of intravitreal anti-VEGF agent injections [8][9][10][11], but this was refuted by other studies [2,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…1 A, B and C). The results of long-term follow-up of these patients showed that 4 patients had a recurrence with CRT ≥ 250 μm, 7 patients did not have a recurrence of macular edema and 3 patients were lost to follow-up after the first review [ 14 ]. These four patients with recurrent macular edema were defined as the recurrence group (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A study showed that combination therapy with IVB and macular laser photocoagulation had fewer effects on BCVA than IVB monotherapy. 50 Another study showed that cataracts and secondary glaucoma were more effective in IVT + GLP compared to the combined effect of IVB + GLP. Still, both treatments were effective in the treatment of macular edema due to branch retinal vascular occlusion.…”
Section: Combination Therapiesmentioning
confidence: 99%